2021
DOI: 10.2147/dddt.s316701
|View full text |Cite
|
Sign up to set email alerts
|

A Network Pharmacology-Based Investigation to the Pharmacodynamic Material Basis and Mechanisms of the Anti-Inflammatory and Anti-Viral Effect of Isatis indigotica

Abstract: Isatis indigotica (Ii) is a cruciferous herb that is widely distributed in China, and its roots and leaves have been used in two renowned antipyretic detoxicate crude drugs in Chinese Pharmacopoeia, Radix (R) and Folium (F) Isatidis. However, the pharmacodynamic material basis and underlying mechanisms of the herbal efficacy remained to be elucidated. Methods: Ultra-performance liquid chromatography-quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF-MS) was adopted for the chemical profiling of R and F Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…In addition, QC samples were employed every 10 injections to monitor the system stability. The mass spectrometer parameters were set according to our previous study with positive-ion as the acquisition mode [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, QC samples were employed every 10 injections to monitor the system stability. The mass spectrometer parameters were set according to our previous study with positive-ion as the acquisition mode [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…In step 1, the AnalysisBaseFileConverter ( , accessed on 16 January 2022) software was used for raw mass spectrum data extraction, and MS-DIAL version 4.24 ( , accessed on 16 January 2022) was used for MS peak detection and alignment with the following parameters [ 10 ]: retention time range, 1–30 min (1–18 min for reference standard samples); retention time tolerance, 0.15 min; MS 1 mass range, 100–1200 (100–1000 min for reference standard samples); MS 1 tolerance, 0.01 Da; MS 2 mass range, 0–1200 (0–1000 min for reference standard samples); MS 2 tolerance, 0.02 Da; minimum peak height, 5000 amplitude (15,000 for reference standard samples). Other parameters, including mass slice width and MS/MS abundance cut off, were set according to our previous study [ 23 ]. An internal standard was used for peak heights normalization.…”
Section: Methodsmentioning
confidence: 99%
“…These effects are thought to occur via a decrease in the NF-κB pathway and an increase in the Nrf2-HO-1 pathway [ 65 ]. Isovitexin also inhibited TNF-α expression in LPS-incubated RAW 264.7 monocyte/macrophage-like cells [ 66 ].…”
Section: Effects Of Individual Phytochemical Components Of ...mentioning
confidence: 99%
“…Chan’s research further implied that isaindigotone derivatives can downregulate c-myc transcription through disrupting the interaction of G-quardruplex and NM23-H2 20 . Recent study indicated that multiple signal pathways, including PI3K-AKT, were involved in the herbal efficacy of I. indigotica 22 . Same parent structure can also be found in PI3K delta inhibitor Idelalisib 23 .…”
Section: Introductionmentioning
confidence: 99%